2011
DOI: 10.1039/c1cc10988j
|View full text |Cite
|
Sign up to set email alerts
|

Chiral properties of tetrathiatriarylmethyl spin probes

Abstract: We report that tetrathiatriarylmethyl (trityl) EPR probes are chiral molecules at room temperature, the two stereoisomers that differ in their helicity being configurationally stable enough to be separated and stored independently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 19 publications
3
40
0
Order By: Relevance
“…7), the paramagnetic analogue of 1 . [16] The experimental and calculated activation enthalpies resulted from our kinetic studies match fairly well the value of Δ H ≠ , which may be derived from the original literature data reported for 7 . In accordance with eq.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…7), the paramagnetic analogue of 1 . [16] The experimental and calculated activation enthalpies resulted from our kinetic studies match fairly well the value of Δ H ≠ , which may be derived from the original literature data reported for 7 . In accordance with eq.…”
Section: Resultssupporting
confidence: 81%
“…This means much shorter half-life for racemization (τ 1/2 = ln2/2 k enant,298 = 8.4 h) in comparison with that for the paramagnetic analogue (28.6 days in ethyl acetate solution [16] ), but it is sufficient to provide the isolation of enantiomerically pure isomers of 1 with of the use of CSP HPLC technique. Thus, a procedure applied by authors of ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Finland trityl, the parent congener of OX063, the three aryl units have a propensity to adopt a C 3 symmetric arrangement, with the aryl units canted parallel to one another, analogous to that found in a three-bladed propeller. 1921 The greater steric congestion combined with possible hydrogen bonding interactions may allow the three aryl units of OX063 to exist in either fully parallel arrangement or with two of the aryl units parallel and one anti-parallel.…”
Section: Resultsmentioning
confidence: 99%
“…5 Conformational studies using EPR spectroscopy, DFT calculation, and X-ray diffraction have shown that the TAMs adopt a helix conformation (Scheme 2) which protects the central carbon bearing approximately 60% of the unpaired electron spin density 66 and provides helicoidally chirality to the EPR spin probe. 67,68 …”
Section: Mutifunctional Assessment Of Chemical Microenvironmentmentioning
confidence: 99%